The development potential of anchor enterprise models in Malawi - Benson, Todd; Cockx, Lara; De Weerdt, Joachim (International Food Policy Research Institute, 2025)
Smallholder-centered agricultural development strategies have had limited success in Malawi over the past several decades. Policy makers are now increasingly looking for alternative ways to accelerate agricultural and rural development. One emerging approach involves larger farms or agri-business firms partnering with smallholder farming households, in what we will refer to as an anchor enterprise model. Support for such partnerships is growing, but there is still little clarity on what they involve, what they aim to achieve and the conditions they need for success. Summarizing findings from a detailed report (Benson, Cockx, and De Weerdt, forthcoming). This policy note seeks to address these questions and provide guidance for future action. We structure our discussion around five questions: what the model is, when it can make sense, for whom it can work, how it can be implemented, and whether it can contribute to inclusive rural development.